The Effectiviness of Word of Wonders in Improving Learning Outcomes and Critical Thinking in Elementary School Students - Ela Nadya Amaliah Husna; Ratnasari Diah Utami (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The purpose of this study is to meet the educational needs of the 21st century, which emphasizes improving learning outcomes and critical thinking skills through the use of up-to-date learning resources. The online game Word of Wonders (WoW) is one of the media used. This objective Surakarta The objective of this study is to evaluate how well WoW helps third-grade students at SD Muhammadiyah 1 Surakarta improve their learning outcomes and critical thinking skills.Methodology: With a one-group pretest-posttest design and 27 students, this study used quantitative methodology. This methodology was used to collect data. The post-test was administered using Word of Wonders after the treatment, while the pre-test was administered before the learning process. In order to use the t-test to assess the data, all instruments underwent validity, reliability, and normality tests.Result: The average score increased significantly from 57.03 on the pretest to 65.18 on the posttest, according to the results. After using WoW, a paired-sample t-test produced a significant value of 0.004 (<0.05), indicating an improvement in language comprehension and critical thinking skills. Students' interest in higher-order thinking skills increased as a result of the game's assistance in vocabulary exploration, word pattern analysis, and logical relationship formation.Applications/originality/value: These research findings provide practical contributions to the development of digital game-based learning as a medium to support Indonesian language learning in elementary schools.